Computer Modeling Of Electromechanical Systems - Sagatov Miraziz Vorisovich (International Journal of Advanced Science and Technology, 2020)
Among modern technical means of industrial, energy and transport purposes, an important role is given toelectromechanical objects. Thanks to the massive use of such objects in various fields of human activity,work has been intensively carried out to improve them over the years. Existing common software forcomputer modeling are characterized by certain opportunities for implementing a structure-orientedapproach. In particular, the representative of such tools is the MatLab / Simulink package. However, itsapplication requires significant preliminary preparation of the simulation problem, which consists increating the appropriate algorithms to supplement the set of functional blocks with new ones, includingalternative ones, which make it possible to efficiently solve the problems posed. A method of structuralalgorithmic modeling of electromechanical systems is proposed, which is an application of a set of modelsimplemented in the form of a library of basic algorithms obtained on the basis of a detailed mathematicaldescription of the processes occurring in the links of electromechanical systems. The main advantages ofthis modeling method are that, firstly, it gives a visual representation of an arbitrarily complex simulatedsystem; secondly, it allows to describe objects in the same way using models of any kind, including pulsetransition or transfer functions, and the rules for connecting individual blocks; thirdly, it makes it possibleto determine the characteristics of the entire system as a whole and its individual parts, to analyze andsynthesize complex objects containing links with both concentrated and distributed parameters.